Adaptación de lentes blandos a paciente de 18 años de edad de sexo masculino con miopía patológica. - Tapia Garzon, Olga Leonor (2022)
The present research work is about an 18 year-old male patient who presents pathological myopia, this type of ametropia is very relevant since the professional optometrist must detect it at an early age, since when an ametropia is not detected in time it can generate more serious problems. severe such as loss of vision. The objective of this clinical case is the adaptation of soft lenses to a myopic patient since he wishes to stop wearing frame lenses since he feels much more comfortable with contact lenses.